Langerhans cell/indeterminate cell histiocytoma. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2010)
We present a case of Langerhans cell histiocytoma and review the relevant literature. A diagnosis of this type should be suspected when facing a congenital nodule, 1-2 cm in size, especially when there is involvement of the epidermis with blisters, erosions or crusts. In case of such a suspicion it is sufficient to perform a biopsy or excision to confirm the diagnosis. Once diagnosed, given the spontaneous regression and the lack of on site or remote recurrences in all the cases reported, you do not need radical surgery and clinical monitoring is sufficient without making any examination potentially harmful to the baby.